2000
DOI: 10.1345/aph.10049
|View full text |Cite
|
Sign up to set email alerts
|

Management of Glucocorticoid-Induced Osteoporosis in Male Veterans

Abstract: Adherence to ACR guidelines for management of glucocorticoid-induced osteoporosis was poor. Efforts to improve the prevention and management of glucocorticoid-induced osteoporosis in male veterans are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Fewer than half of subjects at risk for GIO were dispensed preventive medication, which is consistent with the finding of numerous studies [12][13][14][15][16][17]. Furthermore, the presence of prior femur or vertebral fractures was not associated with GIO prophylaxis.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Fewer than half of subjects at risk for GIO were dispensed preventive medication, which is consistent with the finding of numerous studies [12][13][14][15][16][17]. Furthermore, the presence of prior femur or vertebral fractures was not associated with GIO prophylaxis.…”
Section: Discussionsupporting
confidence: 88%
“…All formulations were converted into prednisone equivalents based on published relative potencies [28]. (e) Clinic type: we classified patients according to whether they had previously been evaluated or treated by rheumatologists or in rheumatology clinics, endocrinologists or in endocrinology clinics, and orthopedic surgeons or in orthopedic clinics, since there is evidence that specialists may perform differently with regard to instituting GIO-preventive measures [14,16,23,29,30]. A single patient visit with these specialists was sufficient to classify subjects.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Fracture of the spine may further worsen respiratory function, 3 and hip fracture is associated with strikingly increased mortality and morbidity, particularly in men. 4 Studies 5 have shown that there is great variability in providers' knowledge about glucocorticoid-induced osteoporosis (GIOP), and many physicians, 6 including those at Veterans Affairs Medical Centers (VAMCs) do not routinely administer agents that may prevent the bone loss complication of glucocorticoid therapy. Osteoporosis is often thought to be a disorder of women; and in the predominantly male population of the typical VAMC, osteoporosis may not be considered a common problem.…”
mentioning
confidence: 99%
“…This may account for the rapid increase in fracture risk. Finally, despite our knowledge of GIOP and the promulgation of guidelines, relatively few people are assessed and treated to prevent fracture [7,8]. Osteoporosis is a silent disorder until there is a fracture.…”
Section: Introductionmentioning
confidence: 99%